Porphyrin Macrocycles: General Properties and Theranostic Potential - Rica Boscencu; Natalia Radulea; Gina Manda; Isabel Ferreira Machado; Radu Petre Socoteanu; Dumitru Lupuliasa; Andreea Mihaela Burloiu; Dragos Paul Mihai; Luis Filipe Vieira Ferreira (Molecules, 2023)
Despite specialists’ efforts to find the best solutions for cancer diagnosis and therapy, this pathology remains the biggest health threat in the world. Global statistics concerning deaths associated with cancer are alarming; therefore, it is necessary to intensify interdisciplinary research in order to identify efficient strategies for cancer diagnosis and therapy, by using new molecules with optimal therapeutic potential and minimal adverse effects. This review focuses on studies of porphyrin macrocycles with regard to their structural and spectral profiles relevant to their applicability in efficient cancer diagnosis and therapy. Furthermore, we present a critical overview of the main commercial formulations, followed by short descriptions of some strategies approached in the development of third-generation photosensitizers.